Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
Solve
1
Add
5
5
5
to both sides of the equation
1
1
−
5
=
2
8
11p-5=28
11p−5=28
1
1
−
5
+
5
=
2
8
+
5
11p-5+{\color{#c92786}{5}}=28+{\color{#c92786}{5}}
11p−5+5=28+5
2
Simplify
Add the numbers
Add the numbers
1
1
=
3
3
11p=33
11p=33
3
Divide both sides of the equation by the same term
1
1
=
3
3
11p=33
11p=33
1
1
1
1
=
3
3
1
1
1111p=1133
4
Simplify
Cancel terms that are in both the numerator and denominator
Divide the numbers
=
3
p=3
p=3
Solution
=
3
so basically yeah p = 3
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.